(untitled) (Transport systems and technologies, 2019)
Based on the analysis of the work of metallurgical enterprises, it is found that practically all the amount of liquid iron goes to the steel workshop, which ensures the use of more high-tech technologies, which should provide more profit from the sale of products. In such circumstances, it is not sensible to elaborate transportation processes to other units when developing simulation models. It is noted that in the conditions of the market, caused by the change in demand, prices for different types of metal products, there may be a need to change the balance of distribution of freight flows of iron to the points of merger. The actual issue of taking into account in the simulation model of all transportations with equally high level of detail is determined. Therefore, the structure of this model has been redesigned and refined, taking into account the work of transport in the blast furnace department. The intensity of cast iron production was set in the model as per the schedule. The design of the experiment is aimed at investigating the effectiveness of various options for transport technologies for the delivery of cast iron at the points of merger of ladles. A factor experiment on a simulation model was performed and the influence on the locomotive utilization rate of the choice of blast furnaces from which cast iron was directed to the pouring machines was determined. Simulation and analysis of the results was performed to determine the most efficient transport technology of the blast-furnace rail area operation in the transportation of liquid iron.